2018
DOI: 10.1016/j.jalz.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk of progression from subjective cognitive decline to mild cognitive impairment: The role of study setting

Abstract: SCD is more likely to progress to MCI in a memory clinic than the general population; participants' characteristics vary across settings. Study setting should be considered when evaluating SCD as a risk state for MCI and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 44 publications
9
101
1
1
Order By: Relevance
“…As shown in this study, Transient SCD can still be relevant, but primarily in the older population and not among the younger individuals. It is possible that in the younger population and in lower-risk individuals (such as in community samples) [ 47 , 48 ], the association between Transient SCD and neurocognitive disorders may be diluted by many other non-neurodegenerative causes such as psychiatric conditions, personality traits, negative self-beliefs, excessive self-attention, and distressing life events [ 43 46 , 49 ]. Possibly, the association between Transient SCD and neurocognitive disorders may only become more apparent when these other non-neurodegenerative causes can be clearly filtered out, such as in the previous study [ 45 ], when the Transient SCD is reported by informant rather than self (and hence we may possibly filter out pure psychiatric or emotional causes that can influence an individual’s subjective reporting of cognitive decline), or such as in the current study, when most of the participants voluntarily visited the ADC to participate in longitudinal studies on cognition (which may have filtered out those without any concerns about cognition) [ 47 49 ] and when the Transient SCD is reported in older rather than younger age (which may have identified those with higher likelihood of neurodegenerative rather than non-neurodegenerative causes of SCD) [ 1 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in this study, Transient SCD can still be relevant, but primarily in the older population and not among the younger individuals. It is possible that in the younger population and in lower-risk individuals (such as in community samples) [ 47 , 48 ], the association between Transient SCD and neurocognitive disorders may be diluted by many other non-neurodegenerative causes such as psychiatric conditions, personality traits, negative self-beliefs, excessive self-attention, and distressing life events [ 43 46 , 49 ]. Possibly, the association between Transient SCD and neurocognitive disorders may only become more apparent when these other non-neurodegenerative causes can be clearly filtered out, such as in the previous study [ 45 ], when the Transient SCD is reported by informant rather than self (and hence we may possibly filter out pure psychiatric or emotional causes that can influence an individual’s subjective reporting of cognitive decline), or such as in the current study, when most of the participants voluntarily visited the ADC to participate in longitudinal studies on cognition (which may have filtered out those without any concerns about cognition) [ 47 49 ] and when the Transient SCD is reported in older rather than younger age (which may have identified those with higher likelihood of neurodegenerative rather than non-neurodegenerative causes of SCD) [ 1 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As these cohorts are community based, it is unclear what the utility of SCD is for identifying Aβ in clinical settings. Because memory‐clinic groups with SCD are at greater risk for clinical progression to AD dementia than the general population [36] (with SCD potentially more informative for clinical progression [37]), it is entirely possible that our estimates may be underestimating the risk for high Aβ in this type of population. Alternatively, SCD endorsement likely underlies the presenting symptom to a memory clinic, thus reducing the utility of a single binary outcome of SCD in this type of population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our sample was community based and participants were not required to have baseline SCC to participate in the study. While we, nonetheless, observed a longitudinal increase in SCC symptoms in our sample, it will be important to evaluate if this effect is even stronger in individuals who report high levels of SCC, such as from a memory clinic setting [38] .…”
Section: Discussionmentioning
confidence: 69%